Identificación de necesidades de capacitación para líderes del sector salud en Montería-Córdoba (2023)
Health institutions require the adoption of strategies that are in accordance with the needs of their leaders and challenges of the environment, in order to remail curret and in the innovation of theircompetences with regard to a better management of the institutions and their different health áreas and provide safety to the patient or user. In such an interpretation, it is necessary to address managerial aspects such as leadership, decisión-making, health quality, planning, biling and auditing in health leaders. For the development of this work, the general objective is to identify the training needs of the leader sor managers of the companies in the health sector in montería, where issues related to these needs and training that is given in each one of them are addressed they. The methodology used was a mixed quantitative and quantitative approach, for which consultations, data collection and information analysis must be carriet out. It is developed study for the training needs in managerial aspects of the leaders of the heralth sector. Seeking to improve their skills in the training or training model.